PIRFENIDONE ATTENUE EPIDURAL FIBROSIS IN RATS BY SUPPRESSING TNF-a , IL-1, AND a-SMA - (:unkn) unknown (My University, 2018)
Aim: Postlaminectomy epidural fibrosis is implicated as a main case of failed back surgery syndrome and associated with increased risk of complications during revision surgery. Various materials or drugs have been used to inhibit formation of epidural fibrosis and reduce the compressive effect on neural structures. Nevertheless, the effects are not satisfied.Pirfenidone is a broad-spectrum anti-inflammatory and anti-fibrotic molecule that has been shown to inhibit the fibrosis progression in patients with idiopathic pulmonary fibrosis and animal models. Anti-fibrotic mechanism of pirfenidone is associated with antagonism of activities mediated by TNF-α and TGF-B. In present study, pirfenidone was studied to investigate its anti-fibrotic effects on reducing epidural fibrosis after laminectomy in a rat model.Methods: Thirty two Wistar albino rats were divided randomly into four equal groups: control spongostan, systemic pirfenidone and local pirfenidone groups. In all groups, total L3-L5 laminectomy was performed. At 4 weeks postsurgery, the animals euthanized and their tissue samples at the laminectomy site were assessed both immunohistochemistry of anti-IL-1, anti- TNF-α and anti-α-SMA antibodies on epidural fibrosis of animal groups and histological evaluation for; dura thickness, epidural fibrosis grading, scar tissue consistency and inflammatory response grading and presence of arachnoid involvement. All data was evaluated by statistically.Results: Our data suggests that rats treated with pirfenidone at 4 weeks post- laminectomy had less , dura thickness, epidural fibrosis, scar tissue consistency and inflammatory response and arachnoidal involvement in comparison with the control and spongostan groups. Pirfenidone treated groups show weaker labeling for anti-IL-1, anti- TNF-α and anti-α-SMA antibodies than control and spongostan groups. Moreover, the local applicaton of pirfenidone had shown better results than systemic administration for all parameters.Conclusion: The results of our study suggested that pirfenidone has anti- fibrotic effects on epidural fibrosis, its effectiveness especially increased when it is used locally.
Keywords: Cerrahi